The Influence of Targeted Profitability and Company Size to Income Smoothing - Izzaty Choirina Mudjiumami; Yuvico MR Setiawan (Journal of Economics, Business, and Government Challenges, 2018)
This research purpose is to know the influence of targeted profitability and company size to income smoothing in manufacture companies listed at Bursa Efek Indonesia period 2015-2017. Method that used for sample target is purposive sampling method. Population of this research are 57 manufacture companies listed at Bursa Efek Indonesia period 2015-2017 which already fulfill the sample criteria that used in this research. To identify companies that did income smoothing practical with using Eckel Index. Result from Eckel Index shown that income smoothing practical also did by a certain companies listed in Bursa Efek Indonesia. Statistic method using multiple linear regression, which are; multicollinearity testing, heteroscedasticity testing, autocorrelation testing, and normality testing. Testing did to proof any significant influence targeted profitability and company size to income smoothing. Research result shown that there is no influence of targeted profitability and company size to income smoothing in manufacture companies listed in Bursa Efek Indonesia period 2015-2017.